Non‐severe haemophilia: Is it benign? – Insights from the PROBE study. (1st September 2020) - Chai‐Adisaksopha, Chatree; Noone, Declan; Curtis, Randall; Frick, Neil; Nichol, Michael B.; Germini, Federico; O'Mahony, Brian; Page, David; Stonebraker, Jeffrey S.; Skinner, Mark W.; Iorio, Alfonso
Abstract: Introduction: There are limited data on the impact of haemophilia on health status and health‐related quality of life (HRQL) in people with non‐severe (mild and moderate) haemophilia. Aim: To evaluate the health status of people living with mild or moderate haemophilia. Methods: Data on respondents with no bleeding disorder (NoBD), mild and moderate haemophilia patients were drawn from the PROBE study. Respondents were enrolled using network patient organizations. This analysis was performed as a cross‐sectional study. Primary outcomes were reported bleeding, acute and chronic pain, activities of daily living and HRQL. Results: A total of 862 respondents with NoBD (n = 173), mild (n = 102) and moderate (n = 134) haemophilia were eligible, with a median age of 33, 42 and 43, respectively. In relation to haemophilia‐related sequalae, 53% of male and 29% of female patients with mild and 83% of males with moderate haemophilia had more than 2‐3 bleeds in the last 12 months. Reporting of acute and chronic pain is less in those with NoBD compared to the mild and moderate cohorts for both genders. Multivariate analysis demonstrates significant reductions in quality of life using VAS, EQ‐5D‐5L and PROBE for males with mild and moderate haemophilia ( P  ≤ .001) with only PROBE indicating a significant reduction for females with mild ( P  = .002). Conclusion: People affected by mild or moderate haemophilia report a significant HRQL impact due to haemophilia‐related bleeding. Future research is needed to identify the optimal care management of patients with mild and moderate haemophilia.